Acceptance and use of information and communication technology in higher education institutes of Kuwait: a proposed framework - Aldaihani, Adel Rashed; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2019)
Information Technology has been effective in every field around the world, and ICT acceptance in any field has produced new developments which has significantly contributed in that particular context. Driven by this impulse the Higher Education Institutes (HEI) around the world are incorporating ICT apparatuses and using the most recent advances to give world class education to inhabitants. In such manner Ministry of Education (MOE) Kuwait has propelled numerous plans and put some considerable measures in the execution of innovation in HEIs. HEIs for the most part comprises of Universities. While there is no comprehensive study conducted in measuring the success and obstacles in the State of Kuwait, therefore, this paper focuses to measure and identify the success factors in acceptance of HEIs in the State of Kuwait. In the interim keeping in mind the end goal to evaluate the adoption and use of ICT by students and academicians in their day by day work, the UTAUT will be used as baseline theory to measure the ICT acceptance by students and academicians. This investigation likewise intends to discover the variables and issues keeping in mind the end goal to make a model for better usage of ICT by in HEIs. The effect of this investigation will be on HEI (s) to enhance the policy of learning methods through successful use of ICT and enhance the ability of students and academicians to be more viable and quality-situated people.